Les images animées au Musée de l'Homme ou la rencontre de deux mondes (1930-1950) - Alice Gallois (Conserveries Mémorielles)
From the origin of cinematograph, many where those who went out of Europe to film otherness. The footage they brought back, whether shown to large audiences in colonial exhibitions or restricted to learned societies, was hardly considered by the scientific community as a valid means of conveying intangible heritage. Yet, from the very heart of the Musée de l'Homme came the most innovating projects aiming to use the cinematographic medium to scientific purposes (research, teaching, production, preservation). The changing attitude of the museum about the role they assigned to cinema between the 1930s and the 1950s accounts for how ambivalent the scientific community is when considering a medium which is usually devoted to fiction – in art or entertainment – while it could be of great help in studying and conveying intangible heritage.